2013
DOI: 10.1089/ars.2012.4563
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nitric Oxide Signaling with nNOS Inhibitors As a Novel Strategy for the Therapy and Prevention of Human Melanoma

Abstract: Aims: Our previous studies have shown that nitric oxide (NO) plays an important role in increasing the invasion and proliferation of human melanoma cells, suggesting that targeting NO signaling may facilitate therapy and prevention. Neuronal nitric oxide synthase (nNOS) is present in melanocytes, a cell type that originates from the neural crest. The aims of this study were to determine the role of nNOS in melanoma progression and the potential antitumor effects of novel synthesized nNOS inhibitors. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 53 publications
(58 reference statements)
4
47
0
Order By: Relevance
“…iNOS has been well characterized in melanoma: its expression promotes cell proliferation; is associated with poor patient survival; and increases resistance to cisplatin [104109]. Although an early study demonstrated nNOS expression in melanocytes and melanoma cells [110], these investigations were not followed up until we recently discovered that nNOS played a role in melanoma invasion and proliferation [111, 112]. The eNOS uncoupling is also an important source of superoxide in melanoma which drives the malignant transformation [113].…”
Section: Rns (Reactive Nitrogen Species) and Ros: A Perspective Rementioning
confidence: 99%
“…iNOS has been well characterized in melanoma: its expression promotes cell proliferation; is associated with poor patient survival; and increases resistance to cisplatin [104109]. Although an early study demonstrated nNOS expression in melanocytes and melanoma cells [110], these investigations were not followed up until we recently discovered that nNOS played a role in melanoma invasion and proliferation [111, 112]. The eNOS uncoupling is also an important source of superoxide in melanoma which drives the malignant transformation [113].…”
Section: Rns (Reactive Nitrogen Species) and Ros: A Perspective Rementioning
confidence: 99%
“…Enhanced production of nitric oxide has previously been shown to play a promoting role in melanomas. [15] So, we chose to screen melanoma cell lines for DDAH-1 levels. Using immunohistochemistry as a semi-quantitative gauge of DDAH-1, DDAH-2 and iNOS concentrations, we assayed a panel consisting of two control melanocyte lines and 64 melanoma cell lines that encompass different stages of malignancy, metastases and mutational status.…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma risk was also found to be increased by MC-1R variant alleles [31,70] suggesting that ROS would be a driver of melanomagenesis [71]. Higher sensitivity of melanocytes from melanoma lesions to oxidizing agents was long demonstrated [71] as well as increased levels of markers of oxidative stress such as O 2 - [72] or NOS [73].…”
Section: Melanomamentioning
confidence: 99%